Dietary Determinants of Cardiovascular Disease in Indonesia: A Narrative Review - Dian Widya Putri (Journal of Global Nutrition, 2025)
Cardiovascular diseases (CVDs) have emerged as a critical public health crisis in Indonesia, accounting for approximately one-third of total national mortality. While clinical management has advanced, the prevalence of heart disease remains high and is increasingly affecting the younger, productive-age population, precipitating an immense economic strain. This narrative review aims to synthesize recent evidence (2017–2023) regarding the multi-dimensional dietary determinants of CVD and evaluate national strategies for risk mitigation. A narrative review design was employed, utilizing a systematic search of PubMed and ScienceDirect databases for English-language literature. Out of 312 identified records, 10 primary studies—including cross-sectional, prospective cohort, and meta-analysis designs—were selected based on robust methodological criteria to analyze the association between dietary intake and cardiovascular risk factors. The synthesis identifies that the Indonesian diet is heavily characterized by excessive refined carbohydrate consumption and high intake of trans-fatty acids (TFA) from fried foods, which act as primary drivers of dyslipidemia. Additionally, findings indicate that animal protein consumption is positively correlated with metabolic syndrome risk in men, whereas isocaloric substitution with plant-based proteins significantly lowers mortality risk. Consequently, the CVD pandemic in Indonesia is fundamentally driven by modifiable nutritional quality issues rather than caloric quantity alone. The study concludes that sustainable risk reduction requires a shift toward plant-based proteins and the implementation of integrated school-based nutritional education to foster long-term behavioral change.